The Role of Sexual Education in Preventive Gender Identity Disorder - Zemouri, Hamida (Technium Social Sciences Journal, 2024)
This current theoritical study aims at highlighting the role of sexual education in preventing sexual identity disorders. This is through: defining the concept, the causes and problems related to these disorders and the role of sexual education in preventing them, using the descriptive approach. The study concluded that sexual education provides teenagers and the youth withfacts about sexual deviations and their harmful effects, in addition to the outcomes resulting from them before establishing a correct sex formation in terms of concept and behavior. In the light of the accomplished results, a set of recommendations were provided most important of which isdefining a general framework for sexual education derived from our religion, civilization and that sexual education is an ongoing and integrated process in the house, at school and in various education-related social institutions.